2017
DOI: 10.1016/j.virol.2016.11.014
|View full text |Cite|
|
Sign up to set email alerts
|

Sinu virus, a novel and divergent orthomyxovirus related to members of the genus Thogotovirus isolated from mosquitoes in Colombia

Abstract: The genome and structural organization of a novel insect-specific orthomyxovirus, designated Sinu virus, is described. Sinu virus (SINUV) was isolated in cultures of C6/36 cells from a pool of mosquitoes collected in northwestern Colombia. The virus has six negative-sense ssRNA segments. Genetic analysis of each segment demonstrated the presence of six distinct ORFs encoding the following genes: PB2 (Segment 1), PB1, (Segment 2), PA protein (Segment 3), envelope GP gene (Segment 4), the NP (Segment 5), and M-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Three unclassified thogotoviruses, Jos virus, Upolu virus, and Aransas virus, fell into clade A, indicating much closer relation to THOV. It is interesting that Sinu virus, an unclassified orthomyxovirus newly isolated from mosquitoes (24), clustered much more closely to baculoviruses than to the other three orthomyxovirus clades. The newly identified BOUV clustered with DHOV.…”
Section: Gp64mentioning
confidence: 99%
“…Three unclassified thogotoviruses, Jos virus, Upolu virus, and Aransas virus, fell into clade A, indicating much closer relation to THOV. It is interesting that Sinu virus, an unclassified orthomyxovirus newly isolated from mosquitoes (24), clustered much more closely to baculoviruses than to the other three orthomyxovirus clades. The newly identified BOUV clustered with DHOV.…”
Section: Gp64mentioning
confidence: 99%
“…During the past decade, advances in DNA sequencing technology have allowed the identification of a wide range of novel viruses associated with mosquitoes (Aguiar et al, 2015; Auguste et al, 2014; Bolling et al, 2015; Carissimo et al, 2016; Chandler et al, 2015; Charles et al, 2016; Cholleti et al, 2016; Coffey et al, 2014; Contreras-Gutierrez et al, 2017; Fauver et al, 2016; Frey et al, 2016; Li et al, 2015a; Li et al, 2015b; Nasar et al, 2012; Ng et al, 2011; Palacios et al, 2015; Pauvolid-Correa et al, 2016; Shi et al, 2015; Simmonds et al, 2017; Vasilakis et al, 2014a; Wang et al, 2015). We examine here, by electron microscopy and metagenomics analysis, 11 mosquito derived viral isolates from the extensive collection of the World Reference Center for Emerging Viruses and Arboviruses (WRCEVA) (https://www.niaid.nih.gov/research/wreceva), whose morphology indicated the likely presence of multi-segmented reoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…A pool of 50 unidentified mosquitoes, designated CoB38d, was triturated in diluent, as described previously ( 3 ). After centrifugation, the supernatant fluid from the insect homogenate was inoculated onto single flask cultures of mosquito (C6/36) and Vero 76 cells that were incubated at 28°C and 37°C, respectively ( 3 ). Cultures were examined daily for evidence of viral cytopathic effect (CPE).…”
Section: Announcementmentioning
confidence: 99%
“…Moderate CPE was observed in the C6/36 culture on the fifth day of incubation; no CPE was seen in the Vero cell culture after 14 days. Supernatant fluid from the C6/36 culture was removed, and the cell monolayer was fixed and subsequently examined by transmission electron microscopy ( 3 ). In ultrathin sections of infected C6/36 cells, multiple double-shelled spherical particles of 45 to 55 nm in diameter were observed in the cytoplasm.…”
Section: Announcementmentioning
confidence: 99%
See 1 more Smart Citation